Character Education in Novels “Dahlan” by Haidar Musyafa: Religious Value and Curiosity Value - Mirfakh, Muhammad Fatwa; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Jurnal Sastra Indonesia, 2024)
Character education is undoubtedly found in many things. They are included in the family and language. Individuals can understand character education by looking at current conditions that shape personalities. Character education can also be found in literary works. In this study, researchers focused only on two character education values, namely religious values and curiosity values in the novel Dahlan by Haidar Musyafa. The research aims to reveal the spiritual and curiosity values of the Darwis character that represent daily behaviors with the quotations obtained. The research approach used by the researcher is literary psychology. The literary psychology approach is a scholarly work created by the author related to the character's character, the character's psychology, and the emotions he writes about. The data collection technique in this study uses heuristics and hermeneutics. It can be concluded that Dahlan's novel by Haidar Musyafa contains positive things that can shape good characters for readers. Character education values include religion and curiosity. The results of the research show and represent that humans always obey their beliefs so that they are always grateful for all the certainties that God gives. The results show and represent humans to always obey their beliefs to be continually thankful for all the certainties God gives. Then, the value of character education in the form of the value of curiosity seeks to reveal the unknown with the meaning of language.